Modeling and evaluation in grinding of SiCp/Al composites with single diamond grain. (November 2019) - Yin, Guoqiang; Gong, Yadong; Li, Youwei; Song, Junli; Zhou, Yunguang
Highlights: A theoretical model of grinding force for single grain grinding SiCp/Al composites is established on the basis of traditional grinding force model. The finite element simulation model of single diamond grain grinding SiCp/Al composites is established. The material removal process for grinding SiCp/Al can be divided into four stages: plastic removal of aluminum matrix, crack initiation of SiC particles, crack growth of SiC particles, and brittle fracture of SiC particles. The transition conditions from ductile to brittle grinding mode of SiC particle are obtained. The UCT has a more significant effect on the grinding force and surface/subsurface quality than the wheel speed. Abstract: In this paper, the theoretical model of grinding force and the finite element simulation model of single diamond grain grinding SiCp/Al aluminum matrix composites were established, and the material removal mechanism was studied, including grinding force, stress distribution and material removal behavior of SiC reinforced particles. The validity of the theoretical model and the finite element model are proved by experiments. The results show that the maximum stress displays smoothly during the removal process of the aluminum matrix, while during the removal process of SiC particles, it fluctuates greatly. Material removal is divided into four stages: plastic removal of aluminum matrix, crack initiation of SiC particles, crack growth of SiC particles, and brittle fracture of SiC particles. The surface defects of grinding SiCp/Al with single diamond grain mainly include voids, microcracks and aluminum matrix delamination. According to the current experimental results, compared to the grinding wheel speed, the undeformed chip thickness (UCT) has more significant influence on the machined surface/subsurface quality. In addition, the removal modes of the SiC particle can be divided into ductile removal, ductile-brittle removal and brittle removal.